PERENCANAAN PEMBANGUNAN DI KECAMATAN LANGGAM TAHUN 2012 - Hidayat, Akbar; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The result of development planning in the district of Langgam in 2012 shows that there ara many planning proposals from the public who are not accommodated well, the proposal in the absence of the proposed project from the bottom, and the approach is top-down planning.The purpose of study is to determine the development planning in the district of Langgam and find out the cause of why the district development planning of Langgam patterned top-down planning.This research used descriptive qualitative research method. The primary data obtained through interview with people who understood local development planning; The secondary data obtained from relevant agencies such as District Office of Langgam and District Development Planning of Regency Pelalawan.The results found that; First, many proposal of public who are not accomodated and not realized by local governments, and inversely proportional to the proposed project arrived-suddenly appread at the end of the discussion of regional development planning. Second, the development planning process that lead to top-down approach, the cause is as follows: First, the public regarded as supporters of the planner is not executing. Second, planning is the desire of the public is not a necessity. Third, the interests of the elite.The Lat, the presence of resource constraints.Key words: Development Planning, District of Langgam, Community